Structure-properties relation of co-dope bismuth layer-structuredBi 3.25La0.75(Ti1-xWx) 3O12 ceramics - Pasinee Siriprapa (2018)
In this work, fabrication and investigation of substituing high-valence W6+ for Ti4+ ion on B-site of La3+-doped Bi4Ti3O12 or BLT structure to form Bi 3.25La0.75(Ti1-xWx) 3O12 or BLTW (when x = 0, 0.01, 0.03, 0.05 0.07, 0.09 and 0.10) ceramics were carried out. X-ray diffraction patterns of BLTW ceramics indicated orthorhombic structure with lattice distortion, especially with higher concentration of WO3 dopant. An increase in WO3 doping content reduced not only length and thickness of grain, but also density of the ceramics. Electrical conductivity was found to decrease, while dielectric constant increased with W6+ doping. Ferroelectric properties were found to be improved with increasing WO3 content and were optimized at x = 0.05. © 2009 World Scientific Publishing Company.